2013
DOI: 10.4049/jimmunol.1301355
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Responses Induced by Lipopolysaccharide Are Amplified in Primary Human Monocytes but Suppressed in Macrophages by Complement Protein C5a

Abstract: Monocytes and macrophages are important innate immune cells equipped with danger-sensing receptors, including complement and Toll-like receptors. Complement protein C5a, acting via C5aR, is shown in this study to differentially modulate LPS-induced inflammatory responses in primary human monocytes versus macrophages. Whereas C5a enhanced secretion of LPS-induced IL-6 and TNF from primary human monocytes, C5a inhibited these responses while increasing IL-10 secretion in donor-matched human monocyte-derived macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
71
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 49 publications
15
71
1
1
Order By: Relevance
“…The C5a-C5aR axis cross-talks with TLR-4 [11] and C5a via C5aR concentration-dependently increases LPS-induced secretion of pro-inflammatory cytokines, including IL-6 and TNF-α in human monocytes [25]. Therefore, the effects of BV on TNF-α and IL-6 were also explored.…”
Section: Discussionmentioning
confidence: 99%
“…The C5a-C5aR axis cross-talks with TLR-4 [11] and C5a via C5aR concentration-dependently increases LPS-induced secretion of pro-inflammatory cytokines, including IL-6 and TNF-α in human monocytes [25]. Therefore, the effects of BV on TNF-α and IL-6 were also explored.…”
Section: Discussionmentioning
confidence: 99%
“…This differential modulation by C5a was further explored in a 2013 study which showed that in response to lipopolysaccharide, C5a enhanced the secretion of proinflammatory cytokines by monocytes, but induced an anti-inflammatory response in macrophages, with production of anti-inflammatory IL-10 (REF. 63). Additional insight has been provided by the observation that CR3 positively modulates lipopolysaccharide-induced responses in myeloid dendritic cells, but not macrophages, by promoting endosome-mediated endocytosis of the TLR required for subsequent signalling 64 .…”
Section: Complement Beyond the Cascadementioning
confidence: 99%
“…C57BL/6 mice, 8-11 wk old, were used in this study (22)(23)(24)(25)(26)(27)(28)(29)(30) g males, 18-25 g females; Charles River Laboratories, Wilmington, MA, USA) and were housed in individually ventilated cages with a controlled 12 h light/dark cycle (lights on 7:00 AM to 7:00 PM) and constant temperature (21 6 2°C). Mice from the same litter were distributed equally between experimental groups, and males and females were treated at the same time.…”
Section: Experimental Animalsmentioning
confidence: 99%